Social assistance and non-agriculture employment in rural China: evidence from the Rural Minimum Living Security (Rural Dibao) - Dian Chen; Xiangming Fang (Humanities & Social Sciences Communications)
Abstract The Rural Minimum Living Security (Rural Dibao) is a crucial social assistance program designed to alleviate poverty in rural China. While non-agriculture employment plays a significant role in boosting farmers’ income and reducing long-term poverty, little is known about the impact of Rural Dibao on non-agriculture employment. This study uses data from the China Household Finance Survey (CHFS) and employs Propensity Score Matching with Difference-in-Differences (PSM-DID) methods to assess the effects of Rural Dibao on non-agriculture employment and to investigate the underlying mechanisms. Our findings reveal that Rural Dibao significantly increases the likelihood of recipients’ participation in non-agriculture employment and extends their labor supply in such jobs. The program primarily boosts temporary work rather than formal employment or self-employment. The increase in temporary employment primarily originated from transitions from agriculture work, rather than from previously unemployed individuals. Mechanism analysis suggests that government-provided employment information and recommendations serve as key drivers for increasing temporary employment, while cash transfers and job-seeking cash subsidies alone do not effectively promote non-agricultural employment.